The enhancement of community perception and participation in gaining sustainable coral reef management models - Widiarti, Riani; Kusumawardhani, Anindita Diah; Burhanuddin, Eko; Susiloningtyas, Dewi; Takarina, Noverita Dian; Patria, Mufti Petala; Fadhilah, Muhammad Faza (Frontiers in Marine Science, 2025)
Coral reef ecosystem plays an important role in climate change mitigation and serves as a crucial source of livelihood, particularly by providing cultural ecosystem services through tourism. Community engagement in the mitigation process is an essential factor in translating policies into action. Therefore, this study aimed to increase the capacity of coastal communities as part of efforts to sustainably manage coral reef ecosystems. To achieve this, semi-structured interviews were conducted to determine community perceptions of the current and future coral reef management. Additionally, training sessions and focus group discussions were held to enhance community capabilities. The results showed that 78% of respondents had a high knowledge level about the ecosystem function. A high perception of coral reef ecosystem management was also observed, indicating community had high expectations for improvement in Lampung Bay.